Contribution of macrophage subpopulations to the pathogenesis of chronic periodontitis in humans and perspectives for study. Review of the literature - V. I. Shynkevych; I. P. Kaidashev (Zaporožskij Medicinskij Žurnal)
The role of macrophages in chronic periodontitis (CP) is essential, but not well understood.